The Inside Mystery of Jejunal Gastrointestinal Stromal Tumor: A Rare Case Report and Review of the Literature - A. K. Dhull; V. Kaushal; R. Dhankhar; R. Atri; H. Singh; N. Marwah (Case Reports in Oncological Medicine)
Gastrointestinal stromal tumors (GISTs) are malignant and rare form of soft tissue sarcoma of the digestive tract. The incidence of gastrointestinal stromal tumors is very low Kramer et al. 2005 Jejunal GISTs are extremely rare. Here we present a rare case of jejunal GIST with unusually large size at presentation. The patient presented with severe abdomen pain, exophytic growth, and dimorphic anemia. Surgical resection of the tumor was carried out, and operative findings revealed a 15 × 10 cm growth, arising from serosal surface of jejunum, at the antimesenteric surface. Diagnosis in this case was made by subjecting the resected specimen to immunohistochemical analysis. In view of large size of the resected tumor, and high-risk histopathological features, imatinib mesylate 400 mg once daily was given as adjuvant chemotherapy. Patient is asymptomatic without any evidence of tumor recurrence after six months of postoperative followup. Imatinib as such is recommended in metastatic, residual or recurrent cases of GISTs or which are surgically not removable; however, recent recommendations suggests the use of imatinib mesylate after radical surgery in high-risk cases, because it has shown a significant decrease in the recurrence rate, and the Food and Drug Administration (FDA) has also approved the use of imatinib as adjuvant therapy after complete resection of localized, primary GIST.